2020
DOI: 10.1016/j.ribaf.2019.101080
|View full text |Cite
|
Sign up to set email alerts
|

Taming the blockchain beast? Regulatory implications for the cryptocurrency Market

Abstract: This paper uses a unique dataset of 120 regulatory events from five classes to test the relevance of the regulatory framework for cryptocurrency value. Time-series market-wide estimates and panel estimates for 300 individual coins and tokens show statistically and economically significant impact of anti-money laundering and issuance regulation. Tighter regulation and more active role of government decrease cryptocurrency prices, evidencing that potentially lower risks and wider adoption commonly attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 29 publications
3
45
0
1
Order By: Relevance
“…Kristoufek [5] found that the price of Bitcoin was significantly and positively correlated with public interests measured by Google Trends and Wikipedia queries, as well as technical indexes, such as hash rates and mining difficulty, in the long run. Moreover, the cryptocurrency market' performance has also been found to be related to media exposure [6,7], policies and regulations [8,9], and other financial assets [10,11], all revealing the inefficiency of the market.…”
Section: Introductionmentioning
confidence: 99%
“…Kristoufek [5] found that the price of Bitcoin was significantly and positively correlated with public interests measured by Google Trends and Wikipedia queries, as well as technical indexes, such as hash rates and mining difficulty, in the long run. Moreover, the cryptocurrency market' performance has also been found to be related to media exposure [6,7], policies and regulations [8,9], and other financial assets [10,11], all revealing the inefficiency of the market.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the technology of transactions in distributed registries virtually eliminates the identification of persons making them. Participants in a distributed registry see only the transaction object (digital asset) but not its owner, whose anonymity is ensured through the creation of a digital wallet (Shanaev, Sharma, Ghimire and Shuraeva, 2020). This wallet is used to record digital assets and is tied to the IP address of a specific computer.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptocurrency has appeared owing to the use of certain technology such as blockchain which makes it possible to exchange resources in electronic form. The idea of implementation and application of such asset as cryptocurrency is stipulated by the elimination of the participation of controlling parties to support certain liveness of the developed infrastructure (Kinash et al, 2019;Andrusiv et al, 2020;Shanaev et al, 2020). At the same time, there is a possibility to exchange resources between the unknown people who do not trust each other.…”
Section: Literature Reviewmentioning
confidence: 99%